Association between non-high-density lipoprotein cholesterol-to-high-density lipoprotein cholesterol ratio and the risk of gestational diabetes: a retrospective study - Guohua Li; Dongxing Su; Wei Huang; Xuehua Wu; Yanzhu Huang (Frontiers in Nutrition)
BackgroundPrevious studies have shown an association between non-high-density lipoprotein cholesterol (non-HDL-C)-to-HDL-C ratio (NHHR) and diabetes; however, its impact on pregnant women remains unclear. This study aims to explore the association between NHHR in early to mid-pregnancy and the incidence of gestational diabetes mellitus (GDM).MethodsThis study retrospectively collected and analyzed prenatal examination data from pregnant women. Variables were selected using least absolute shrinkage and selection operator (LASSO) regression and multivariable logistic regression, and the association between NHHR and GDM incidence was assessed through sensitivity and subgroup analyses. Propensity score matching (PSM) was applied to reduce selection bias between groups. Additionally, receiver operating characteristic (ROC) analysis was performed to assess the predictive accuracy of NHHR for GDM.ResultsThe study included 572 pregnant women aged 20–44 years, with a mean age of 31.35 years (standard deviation: 4.02). LASSO and multivariable logistic regression analyses identified NHHR as an independent risk factor for GDM. Despite adjusting for group differences using PSM, NHHR values remained significantly different between groups (p = 0.009). The predictive accuracy of NHHR for GDM was 0.625 [95% confidence interval (CI): 0.570–0.679]. Multivariable logistic regression analysis revealed a significant positive association between NHHR and GDM (odds ratio: 2.25; 95% CI: 1.27–3.98). Furthermore, the association between NHHR and GDM appeared linear (P for non-linearity > 0.05), and the positive correlation remained consistent across most subgroups.ConclusionThis study suggests that an elevated NHHR is associated with an increased risk of GDM. Early measurement of NHHR could help identify women at risk for GDM, potentially enabling timely interventions to improve pregnancy outcomes.